2011
DOI: 10.3109/03008207.2011.628765
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Joint Loading Reduces Degenerative Actions of Matrix Metalloproteinases in the Articular Cartilage of Mouse Ulnae

Abstract: Joint loading is a recently developed loading modality, which can enhance bone formation and accelerate healing of bone fracture. Since mechanical stimulation alters expression of matrix metalloproteinases (MMPs) in chondrocytes, a question addressed herein was, does joint loading alter actions of MMPs in the articular cartilage? We hypothesized that expression and activity of MMPs are regulated in a load–intensity-dependent manner and that moderate load scan downregulates MMPs. To test this hypothesis, a mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 29 publications
(30 reference statements)
2
31
0
Order By: Relevance
“…Our previous studies revealed that CITED2 plays a critical chondroprotective role by suppressing MMP13 at the gene and protein levels . CITED2 responds to multiple stimuli, including cytokines and mechanical stress . In this study, we provided evidence that the anti‐inflammatory cytokine IL‐4 induces CITED2 expression in human chondrocytes.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Our previous studies revealed that CITED2 plays a critical chondroprotective role by suppressing MMP13 at the gene and protein levels . CITED2 responds to multiple stimuli, including cytokines and mechanical stress . In this study, we provided evidence that the anti‐inflammatory cytokine IL‐4 induces CITED2 expression in human chondrocytes.…”
Section: Discussionmentioning
confidence: 57%
“…We have previously demonstrated that moderate loading induces CITED2 gene expression and exerts a chondroprotective effect, at least in part, through repressing MMPs such as MMP13 in vitro and in vivo . We therefore examined the effect of mechanical loading in combination with IL‐4 on MMP13 expression in human OA primary chondrocytes in the presence of IL‐1β.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mechanotransduction pathways underlying chondroprotection are not well understood, recent studies have shown that biomechanical signals inhibit multiple steps in the IL-β-induced cascade downstream of IκB kinase activation, regulating IκB-α and IκB-β degradation and synthesis and promoting IκB-α shuttling to export nuclear NF-κB and terminate its transcriptional activity. 12 Furthermore, induced by dynamic moderate loading, such as joint motion and joint loading in the lateral/medial direction in vivo, 5,13 and by moderate fluid shear and intermittent hydrostatic pressure in vitro, 5,14 transactivated transcriptional factor CITED2 leads to the suppression of MMPs, at least in part through competition with MMP transactivator Ets-1 for binding to coactivator p300. 2,5 Moreover, transient receptor potential vanilloid 4 (TRPV4), a Ca 2+ -preferred membrane ion channel, acts as a transducer for loading-induced chondrocyte matrix biosynthesis.…”
Section: Mechanotransduction Of Chondroprotectionmentioning
confidence: 99%
“…Previous studies suggested that moderate exercise, or mechanical loading within a physiologic range, exerts chondroprotection through, at least in part, the upregulation of the transcriptional regulator Cbp/p300 interacting transactivator with Glu/Asp‐rich carboxy‐terminal domain 2 (CITED2) in joint tissue cells such as chondrocytes and synoviocytes . These studies showed that CITED2 represses the expression of matrix metalloproteinases (MMPs) such as MMP‐13 . However, it is unknown whether CITED2 is also mechanosensitive and plays role in the regulation of adipokine expression in adipose tissues such as the IPFP.…”
Section: Introductionmentioning
confidence: 99%